2021
DOI: 10.17219/dmp/141521
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the timing of dental care in Peruvian children

Abstract: Background. Due to the high transmissibility of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 , governments adopted preventive measures, such as social distancing and obligatory social immobilization, which negatively affected access to health services, including oral health services. Similarly, dental care restraint arose in this context, with the aim of reducing the possibility of cross-infection caused by aerosols, which notably restricted dental care ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The scientific evidence developed from health emergency reports that the time since the last dental care in Peruvian children would have increased by 1.39 years, indicating that this dilation in the search for timely care would be associated with the year of the pandemic, noting that in previous years, variables such as place of dental care, natural region of residence and age already showed significant differences, but the year itself denotes greater relevance. 25 Regarding toothbrushing, it was observed that the pandemic harmed its daily practice at least twice daily, which could be explained by the complex context faced by the country due to multiple measures to contain contagions that impacted the economy and social habits of Peruvian households, so that more pressing aspects may have been prioritized, rather than a preventive habit; similarly, it was found that factors such as geographic region, area and place of residence, altitude, health insurance coverage, economic level, age, and sex were associated with brushing. 26 Among the limitations of this research is the use of secondary information sources such as the ENDES survey, where the information collected could present inaccuracies due to self-reporting.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific evidence developed from health emergency reports that the time since the last dental care in Peruvian children would have increased by 1.39 years, indicating that this dilation in the search for timely care would be associated with the year of the pandemic, noting that in previous years, variables such as place of dental care, natural region of residence and age already showed significant differences, but the year itself denotes greater relevance. 25 Regarding toothbrushing, it was observed that the pandemic harmed its daily practice at least twice daily, which could be explained by the complex context faced by the country due to multiple measures to contain contagions that impacted the economy and social habits of Peruvian households, so that more pressing aspects may have been prioritized, rather than a preventive habit; similarly, it was found that factors such as geographic region, area and place of residence, altitude, health insurance coverage, economic level, age, and sex were associated with brushing. 26 Among the limitations of this research is the use of secondary information sources such as the ENDES survey, where the information collected could present inaccuracies due to self-reporting.…”
Section: Discussionmentioning
confidence: 99%
“…During this health emergency, the use of non-COVID-19 health services has declined across the board, especially in low- and middle-income countries [ 22 ]. From a dental perspective, access to these services has also been impaired, compromising the timely utilization of oral health services in Peruvian children [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the results presented are before the coronavirus disease pandemic (COVID-19), which may have varied due to the impact that the pandemic has had on oral health indicators such as access to dental care, which increased by more one year according to previous study. 25 However, these results should be considered by those who make public health policies, specifically by those responsible for oral health at the national level in Peru and countries in the region, so that they can evaluate how geographical barriers may limit the establishment of oral health practices such as the use of fluoridated toothpastes; these policies to close inequality gaps will allow for better oral health in the population.…”
Section: Discussionmentioning
confidence: 99%